TRANSLATION TRAINING OF FUTURE PHILOLOGISTS USING MODERN INFORMATION TECHNOLOGIES - Прохоров, Микола Георгійович (AD ALTA, 2024)
Abstract: The article represents an attempt to systematize specific features of translation training of future philologists within the environment of digital transformation. Special attention is paid to the necessity of shaping in future graduates the competence sufficient to effectively work in the sphere of B2B translation services. A concept of today integrative competence of future philologists-translators is covered and the need to apply a cross-disciplinary approach to designing curricula for teaching translation is emphasized. Core specifics and challenges of teaching localization is investigated in detail, based on both theoretical provisions and case studies. A potential of gamification and AI/ML application in translation training is outlined.
The digital educational environment is the reality in which modern society lives today. In the digital learning environment, students in higher educational institutions develop many important qualities and skills that are in demand by 21st century society. They determine the personal and social status of a modern person: information activity and media literacy, the ability to think globally, the ability for continuous education and solving creative problems, willingness to work in a team, communication and professional mobility. Therefore, it is not difficult to imagine that the next period in professional education will be devoted to the formation of a new generation of specialists who have digital competencies and are ready to function in the digital space of modern society [25]. Consequently, the vocational education system will be modernized, and there will be a need to provide educational institutions with modern equipment, digital educational technologies, and relevant teaching staff capable of transforming the entire educational process.
Keywords: translation training, digital transformation, IT, gamification, localization, competence